Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
đề sai , sửa lại : -2+8-12+18-22+28-....-92+98
[(-2)+8]+[(-12)+18]+[(-22)+28]+....+[(-92)+98]
= 6 x [(98-8) / 10+1]
= 6 x 10
= 60
A = \(\dfrac{18}{26}\) + (-\(\dfrac{5}{27}\)) + (-\(\dfrac{22}{86}\)) + \(\dfrac{12}{39}\) - \(\dfrac{32}{43}\)
A = \(\dfrac{9}{13}\) - \(\dfrac{5}{27}\) - \(\dfrac{11}{43}\) + \(\dfrac{4}{13}\) - \(\dfrac{32}{43}\)
A = (\(\dfrac{9}{13}\) + \(\dfrac{4}{13}\)) - (\(\dfrac{11}{43}\) + \(\dfrac{32}{43}\)) - \(\dfrac{5}{27}\)
A = \(\dfrac{13}{13}\) - \(\dfrac{43}{43}\) - \(\dfrac{5}{27}\)
A = 1 - 1 - \(\dfrac{5}{27}\)
A = 0 - \(\dfrac{5}{27}\)
A = - \(\dfrac{5}{27}\)
1/ -7264 + (1543 + 7264)
=-7264 + 1543 + 7264=1543
2/ (144 – 97) – 144
=144-97-144=-97
3/ (-145) – (18 – 145)(Vì có dấu trừ ở trước ngoặc nên p đổi dấu)
=-145-18+145=-18
4/ 111 + (-11 + 27)
=111-11+27=137